Functions of musical theory in the actor’s training - Ivanova, Assia (Young Scientific Music and Dance Forum : Conference with international participation, 2020)
The development of modern theater poses new challenges for the actor and the means of expression he has. The terms rhythm, tact, timbre, melody, tempo – belonging to the musical theory – become obligatory in the theoretical and practical arsenal of the actor. Interactions with music are obvious when we work with a particular musical form or working with musicality of the dramatic text in the show. The musical elements, however, are present not so obvious in the actor’s work, even without himself realizing it. They are most recognizable in constructing the vocal and physical character of the image, and their conscious use in the creative process would help „create the life of the human body (of the role).“ [Stanislavski 2016, p. 189]. One of the main aims of this text is to focus on certain interrelations between musical theory and the actor’s work on the stage image. Also presents in part the methodology of teaching and various practical developments, which support the theoretical introduction to musical theory (in the training of acting at NBU) and its application in practice of the actor.